Long-term antibiotic therapy in late onset pouch-urethral fistula after ileoanal anastomosis for ulcerative colitis may be effective and well tolerated. (15th March 2013) - Samaha, Mario; Moloney, Manus
Abstract : A 25-year-old male patient underwent restorative proctocolectomy and ileoanal anastomosis in 1991 for refractory ulcerative colitis. In February 2001, he presented with pneumaturia, faecaluria, pelvic 'pressure' and watery diarrhoea caused by passage of urine through the anal canal. A fistula between the pouch and the membranous urethra was demonstrated by a pouchogram contrast study. In October 2002, he was started on ciprofloxacin 250 mg once daily and metronidazole 400 mg twice daily. Apart from a short break in 2003 the patient has remained on this regimen until the time of writing (now over 10 years) and has had sustained remission, excellent quality of life and no adverse effects.